KONSEP MANUSIA DALAM PEMIKIRAN IBNU KHALDUN - Riza Chamadi, M. (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
Humans are unique creatures, possessing two elements that are physical and spiritual. The two elements need to be further explored in the human concept. Al-Quran divides human into four categories, namely An-Nas, Basyar, Man, and Insan. in the frame of Ibn Khaldun's thinking, he describes human beings into two categories as commonly as human beings as a physical and spiritual form. Ibn Khaldun then describes with various approaches and analysis is so beautiful that suggests that humans are creatures of intellect and traditional creatures.Key Words: Human, al-Qur'an, Ibn Khaldun